2016
DOI: 10.1177/0306624x16644500
|View full text |Cite
|
Sign up to set email alerts
|

The Views of the Public on Youth Offenders and the New Zealand Criminal Justice System

Abstract: Public perceptions of crime and punishment have taken on increasing importance as countries grapple with how to address youth violence. The current study aimed to compare the views of those who have had personal experience of victimisation from youth offenders and those who have not, on what could be improved in managing youth offending in New Zealand. A qualitative methodology was used with data from open-ended survey responses from a nationally representative sample. Public sentiments favoured addressing sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 67 publications
4
15
0
Order By: Relevance
“…A number of studies have investigated public attitudes toward various facets of the criminal justice system in New Zealand. Over the past two decades, attitudes toward crime have received scholarly attention (see Bratcher, 1997; Paulin, Searle & Knaggs, 2003), as well as rural crime rates (see Buttle & Rodgers, 2014), and different types of criminal offenders such as tax evaders (see Marriott, 2017; Marriott & Sim, 2016; 2017), sex offenders (see Thakker, 2012; Willis, Malinen, & Johnston, 2013), youth offenders (Barretto, Miers, & Lambie, 2018), and drivers under the influence of drugs (Malhotra, Starkey, & Charlton, 2017). Brookman and Wiener (2017) used an online survey to investigate public perceptions toward predicting punitive attitudes to sentencing in Australia.…”
Section: Cultural Legacies: Intuitional Link To Public Perceptionsmentioning
confidence: 99%
“…A number of studies have investigated public attitudes toward various facets of the criminal justice system in New Zealand. Over the past two decades, attitudes toward crime have received scholarly attention (see Bratcher, 1997; Paulin, Searle & Knaggs, 2003), as well as rural crime rates (see Buttle & Rodgers, 2014), and different types of criminal offenders such as tax evaders (see Marriott, 2017; Marriott & Sim, 2016; 2017), sex offenders (see Thakker, 2012; Willis, Malinen, & Johnston, 2013), youth offenders (Barretto, Miers, & Lambie, 2018), and drivers under the influence of drugs (Malhotra, Starkey, & Charlton, 2017). Brookman and Wiener (2017) used an online survey to investigate public perceptions toward predicting punitive attitudes to sentencing in Australia.…”
Section: Cultural Legacies: Intuitional Link To Public Perceptionsmentioning
confidence: 99%
“…; Piquero and Steinberg ; Roberts and Hough ). A recent study of New Zealand public opinion on how young offenders should be dealt with found that those surveyed supported rehabilitative and preventive measures for young offenders, with victims of crime having less punitive attitudes than non‐victims (Barretto, Miers and Lambie ). However, the views of the public on the appropriate response to murder by young persons is less clear.…”
Section: Public Sentimentmentioning
confidence: 99%
“…A large body of research internationally finds public support for rehabilitation of young offenders (Nagin et al 2006;Piquero and Steinberg 2010;Roberts and Hough 2005). A recent study of New Zealand public opinion on how young offenders should be dealt with found that those surveyed supported rehabilitative and preventive measures for young offenders, with victims of crime having less punitive attitudes than non-victims (Barretto, Miers and Lambie 2016).…”
Section: Public Sentimentmentioning
confidence: 99%
“…Attitudinal variables are thought to be relevant for answering some of the key questions in the criminal justice system (Barretto, Miers, & Lambie, 2018; Chui, Cheng, & Ong, 2015; Chui, Cheng, & Wong, 2013; Gottlieb, 2017; Ortet-Fabregat, Perez, & Lewis, 1993). Therefore, more emphasis has been placed on the study of attitudes toward crime and criminals in recent years.…”
Section: Introductionmentioning
confidence: 99%